A mutação da natureza jurídica da reclamação em razão da política judiciária das cortes superiores - Peleja Júnior, Antônio Veloso (2018)
The complaint is a particular legal institute of Brazilian law whose mission is to ensure the jurisdiction and the consolidated understanding of the courts. The new Code of Civil Procedure, considerate on the proposition of these jurisprudential positions and on the "enforcement" of its observance by the court, expanded the operation of the complaint of article 988 assigning it as a guarantor of these understandings, which were qualified as "precedents". The channeling of a considerable number of complaints to higher courts forced, in the name of judicial policy and administration, the generation of atypical solutions to the situation, given the anomy in the discipline of the legal institute and the counter-claim represented by the prevalence of the quantitative aspect over the qualitative one. The transformation of the legal nature of the complaint to meet the demands of higher courts is performed by trampling on some constitutional and infra-constitutional principles, in a rearrangement of competences and appropriateness, which does not conform to the scenario of civil procedural law, recipient of the radiant efficacy of the Federal Constitution. On the other hand, after several years of constitutional and procedural reforms aimed at mitigating the workload of these Courts - which ended up by adjusting them more as thesis reductions than as a decrease of analysis of thousands of concrete cases - the procedural status quo of the complaint meets these changes. Resolutions no. 9/2012 and n. 3/2016 summarize a pool of legal institutes, regulations and judicial policies that should be properly analyzed before having their admission accepted into the Brazilian legal system besides proposing a solution to the status quo judicially constituted